The use of internet-based social media as a tool in enhancing student's learning experiences in biological sciences - Maribel Beltran Cruz; Shannen Belle B. Cruz (Laureate Education Inc, 2013)
This study explored the use of social media as a tool in enhancing student's learning experiences, by using online instruction as a supplement to a face-to-face general education course, such as biological sciences. Survey data were collected from 186 students who were enrolled in a Biological Sciences course. The course was taught in a blended format using Facebook and Edmodo online social networks. A four point Likert scale was used to interpret the data collected. Findings indicated that, when traditional face-to-face instruction was combined with online components, students' learning was enhanced. Findings from this study indicate that students had better experience, better engagement, and appreciated both the social learning experience gave by the online social network. Results revealed that students through student-student interaction and student-teacher interaction enhance their own experiences and improved their learning ability. The findings were used as bases in developing new practices and methodologies involving social networking tools for learning. Moreover, findings were used to design a blended format syllabus and blended learning guidelines.   DOI: 10.18870/hlrc.v3i4.170